Diversification of Rosaceae since the Late Cretaceous based on plastid phylogenomics - Zhang, Shu‐Dong; Jin, Jian‐Jun; Chen, Si‐Yun; Chase, Mark W.; Soltis, Douglas E.; Li, Hong‐Tao; Yang, Jun‐Bo; Li, De‐Zhu; Yi, Ting‐Shuang (The New phytologist, 2017)
Phylogenetic relationships in Rosaceae have long been problematic because of frequent hybridisation, apomixis and presumed rapid radiation, and their historical diversification has not been clarified. With 87 genera representing all subfamilies and tribes of Rosaceae and six of the other eight families of Rosales (outgroups), we analysed 130 newly sequenced plastomes together with 12 from GenBank in an attempt to reconstruct deep relationships and reveal temporal diversification of this family. Our results highlight the importance of improving sequence alignment and the use of appropriate substitution models in plastid phylogenomics. Three subfamilies and 16 tribes (as previously delimited) were strongly supported as monophyletic, and their relationships were fully resolved and strongly supported at most nodes. Rosaceae were estimated to have originated during the Late Cretaceous with evidence for rapid diversification events during several geological periods. The major lineages rapidly diversified in warm and wet habits during the Late Cretaceous, and the rapid diversification of genera from the early Oligocene onwards occurred in colder and drier environments. Plastid phylogenomics offers new and important insights into deep phylogenetic relationships and the diversification history of Rosaceae. The robust phylogenetic backbone and time estimates we provide establish a framework for future comparative studies on rosaceous evolution.